Evaluación del extracto acuoso de semilla de higuerilla (Ricinus communis l.) Como herbicida presiembra para el control de malezas en el cultivo de chocho (Lupinus mutabilis sweet) en el Barrio Santan grande de la parroquia Ignacio Flores Del Cantón Latacunga. - Chusin Ayala, Lidia Paulina (2020)
The research was carried out in Santan Grande neighborhood, Ignacio Flores Parish, Latacunga Canton, with the aim of evaluating the effect of the aqueous extract of Higuerilla seed (Ricinus communis L.) for the pre-sowing control of weeds in the crop of chocho. For this, a divided plots design was used that consisted of 6 treatments with three repetitions with a total of 18 experimental units.The total area of the research was 215 m2. It was proposed the characterization from the botanical point of view and the raw material used for the elaboration of the organic herbicide. It was determined the most effective dose of the aqueous extract of fig seed in the control of weeds in pre-sowing of the chocho crop, and the cost of implementation of three herbicides.In the field, it was evaluated the percentage of weed control per determined area and incidence of weeds, which were evaluated by the quadrant method at 7, 14 and 21 days. Obtaining the following results; the collected vegetal material corresponds to the species Ricinus communis L. of the Ecuadorian White variety. Respect to the population index of arvenses the presence of 16 species was found.For the percentage of survival and final control it was registered in T1: 47% survival and 53% control. In T2: 86% survival with a 15% control, in T3: 122% survival and -22% control. In T4: 115% survival and -15% control, for T5: 0% survival with a 100% control. Finally in T6: 10% survival with a 90% control of the initial population of arvense